1H- AND 13C-NMR SPECTRA OF SOME AZOMETHINES OF 5-AMINO-2-PHENYLINDOLE SERIES - Tai, Dang Nhu; Thanh, Nguyen Dinh; Nam, Pham Duy; Duc, Hoang Thanh (Vietnam Journal of Chemistry, 2014)
The 1H- and 13C-spectra of some azomethines of 5-amino-2-phenylindole series have been recorded and researched. It shown that, the substituents in benzene ring influenced on the chemical shift of proton on azomethine bond